2016
DOI: 10.1093/ndt/gfw058
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol delays polycystic kidney disease progression through attenuation of nuclear factor κB-induced inflammation

Abstract: The NF-κB signaling pathway is activated and partly responsible for inflammation in polycystic kidney tissues. Targeting inflammation through resveratrol could be a new strategy for PKD treatment in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 35 publications
0
39
1
Order By: Relevance
“…Based on these data, we hypothesize that IRF5 ASO treatment reduces cystic index by reducing the ability of macrophages to produce cystpromoting cytokines such as TNFa and IL-6 (26). Both of these cytokines, and their associated downstream signaling pathways including p-STAT3, are expressed in renal macrophages (33,34) and have been implicated in progression of cystic disease (35)(36)(37)(38). To test this hypothesis, we flow sorted Figure 3.…”
Section: Suppression Of Irf5 Reduces Macrophage Proinflammatory Cytokmentioning
confidence: 99%
“…Based on these data, we hypothesize that IRF5 ASO treatment reduces cystic index by reducing the ability of macrophages to produce cystpromoting cytokines such as TNFa and IL-6 (26). Both of these cytokines, and their associated downstream signaling pathways including p-STAT3, are expressed in renal macrophages (33,34) and have been implicated in progression of cystic disease (35)(36)(37)(38). To test this hypothesis, we flow sorted Figure 3.…”
Section: Suppression Of Irf5 Reduces Macrophage Proinflammatory Cytokmentioning
confidence: 99%
“…Resveratrol (RES) is naturally occurring plant antibiotic known as phytoalexin, found in various plants, nuts, fruits and especially abundant in grapes and red wine1617. It has been extensively studied for its antioxidant, anti-aging and anti-inflammatory activities181920212223. In addition, in vivo and in vitro studies showed that RES possesses potential anti-tumor activity against several malignancies24252627.…”
mentioning
confidence: 99%
“…Additionally, resveratrol activates the AMP-activated protein kinase (AMPK) signaling pathway, which again is related to the activation of PGC-1α levels and the beneficial effects of resveratrol on mitochondrial function [88,89]. Furthermore, in a recent study, treatment with resveratrol showed promising results for the delay in PKD progression in Han:SRPD:PKD rats by inhibiting inflammation [90]. These preliminary observations will prompt further research in ADPKD patients [85].…”
Section: Mitochondrial Dysfunction In Adpkdmentioning
confidence: 96%